2015
DOI: 10.1111/jfr3.12132
|View full text |Cite
|
Sign up to set email alerts
|

Household measures for river flood risk reduction in the Czech Republic

Abstract: Interviews with 304 households were used to determine flood risk reduction measures adopted in the case study of the Becva River in the Czech Republic. Uptake of measures was low, irrespective of experience with floods. Financial cost seemed to be a barrier towards implementation, but more work is needed to understand the combination of factors limiting adoption of household flood risk reduction measures. Regression analysis indicated that socio-demographic factors play an important role in household decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 47 publications
(80 reference statements)
2
58
1
2
Order By: Relevance
“…9 FEMA's official stance is that "no home is completely safe from potential flooding devastation" (https://www.fema.gov/ national-flood-insurance-program) and designates zones as low risk but not as no risk. This is also true in other nations (e.g., Duží et al 2017). 10 This is unlikely true in the long run in light of climate change.…”
Section: Modelmentioning
confidence: 98%
“…9 FEMA's official stance is that "no home is completely safe from potential flooding devastation" (https://www.fema.gov/ national-flood-insurance-program) and designates zones as low risk but not as no risk. This is also true in other nations (e.g., Duží et al 2017). 10 This is unlikely true in the long run in light of climate change.…”
Section: Modelmentioning
confidence: 98%
“…In the CR, there are few studies complementing the collected flood expenditure data with microeconomic evidence. Duzi et al (2014) revealed that Czech households that experience increasing flood damages did not implement more self-protection. Furthermore, Raška and Brázdil (2015), p. 13) conclude their historical examination of riskreduction measures in Bohemia as follows: '…[M]otivation to adopt private mitigation measures in the postcommunist countries is low because of the centralisation and institutionalisation of the risk reduction strategies during the communist period'.…”
Section: Discussion Of Data Availability For Indication Of the Crowdimentioning
confidence: 99%
“…European floods in 2013 and Central European floods events in 1997, 2002(Socher and Böhme-Korn, 2008Vávra et al, 2015). The Czech Republic experienced numerous knowledgeable floods in 1997, 1998, 2002, 2006(Vávra et al, 2015Duží et al, 2017). Extreme flood events can affect naturally occurring fish species in rivers (Horwitz, 1978;Poff and Allan, 1995;Gordon et al, 2004), as well as overall fish stocks and cause considerable losses of fish populations in ponds.…”
Section: Introductionmentioning
confidence: 99%